Exploring the academic experience of college student survivors of sexual violence: a phenomenological inquiry - Lorenzo, Lorisa, author; Anderson, Sharon K., advisor; Chesson, Craig, committee member; Haddock, Shelley, committee member; Kuk, Linda, committee member (Colorado State University. Libraries, 2019)
Approximately 21% of female undergraduates and 7% of male undergraduates report being sexually assaulted while in college (Krebs et al., 2016). Student survivors of sexual violence experience negative impacts on their academic performance, which can result in a lower grade-point average (GPA) and a decision to leave the institution where the incident occurred (Baker et al., 2016). To gain a better understanding of the academic experience of college student survivors of sexual violence, the author conducted a qualitative phenomenological study using the descriptive phenomenological psychological method developed by Giorgi (Giorgi, 2009) to answer the following research question: "How do college student survivors of sexual violence describe their academic experiences following an incident of sexual violence?" Six currently enrolled undergraduate college students completed semistructured interviews to explore their lived academic experiences following an incident of sexual violence. In-depth analysis of the data revealed the following essential constituents of the academic experience of participants following the incident of sexual violence: negative emotional and mental health consequences, shame and self-blame, isolation from classmates and professors, impaired ability to focus on academic tasks, losing motivation and questioning academic goals, finding ways to cope, healing and reconnection, and academic identity as more than GPA. These essential constituents constitute the general structure of the academic experience of participants following an incident of sexual violence. Results of the study provide a deeper understanding the psychological mechanisms through which sexual violence negatively impacts the academic experience of college student survivors of sexual violence.
Keywords: academic performance; higher education; sexual violence; college students; academic experience; sexual assault